Effect of blade width on ultra-low specific speed axial turbines. Issue 3 (14th September 2022) - Du, Yang; Qasim, Mohammed A.; Li, Yanpin; Velkin, Vladimir I.; Chen, Dexin
ABSTRACT: Ultra-low specific speed axial turbines for cooling tower have some issues, such as low head, low efficiency, and turbulent internal flow. According to the orthogonal experiment and CFD analysis, it was found that the blade width was the main factor affecting the head, while the numbers of stay vanes and blades were the main factors affecting the efficiency. To further optimize the hydraulic performance of ultra-low specific speed axial turbines, six models of ultra-low specific speed axial turbines with different blade widths were designed. CFD numerical simulations showed that at different flow rates, with increasing blade width, the head gradually decreases and the efficiency shows a trend of first increasing and then decreasing. For the ultra-low specific speed axial turbine designed in this paper, when the blade width is 35 mm, the water head is 6.75 m, which meets the requirements of cooling tower turbines on head. At this blade width, the turbine achieves the highest efficiency of 81.15%, its flows are uniform, performance is stable. The internal flow field and pressure distribution of the runner are in better agreement with the design indexes of an ultra-low specific speed axial turbine. Thus, a high-efficiency ultra-low specific speed axial turbine suitable for cooling tower residual energy recovery is preferably selected.